Analisis Edukasi Positive Discipline Pada Konten Parenting Akun Instagram @Haibundacom - Cakranegara, Muhammad Bintang; Nursanti, Siti; Nayiroh, Luluatu (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Positive discipline education is an approach aimed at building children's discipline through positive and supportive communication without involving harsh punishment. The Instagram account @Haibunda.com utilizes social media to provide educational content on parenting, helping parents understand the importance of positive discipline in shaping children's behavior. This study aims to analyze the content of positive discipline education messages in parenting on the Instagram social media account @Haibunda.com, targeting its audience, especially young mothers. The method used in this study is a qualitative research method with a descriptive approach, through content analysis of posts on the Instagram account @Haibunda.com from July to September 2024. The findings show that the account uses attractive visual illustrations, infographics, and short videos to facilitate parents’ understanding of positive discipline concepts, such as the importance of empathy, open communication, and the development of supportive relationships with children. The education delivered through this account is expected to help parents develop a more effective and empathetic parenting approach. The results of this study reinforce the New Media theory and the role of social media as a digital communication tool that impacts modern parenting practices.